Advanced marginality in the Metropolitan Area of San José, case studies of: Alajuelita, Los Guido and Pavas (1986-2011) - Blanco Ramos, Roberto Antonio (2024)
This article investigates the historical development of a phase of advanced marginality in the Metropolitan Area of San José. To examine this process, emphasis is placed on the socio-historical construction of territorial stigmatization in the canton of Alajuelita, the district of Los Guido, in Desamparados and in the district of Pavas. To achieve this, the proposals of urban sociology developed by Loïc Wacquant are used and are approached from a historical perspective. In methodological terms, the research proposes a qualitative approach through descriptive and content analysis of primary sources and the conduct of an unstructured interview. For the quantitative part, population censuses from the study period are analyzed. The text concludes thatadvanced marginality was constituted through the incidence of interwoven hegemonic policies: neoliberalism and actions to address territorial inequalities in relation to housing.